2010
DOI: 10.1088/0031-9155/55/8/016
|View full text |Cite
|
Sign up to set email alerts
|

Experimental investigation of factors affecting the absolute recovery coefficients in iodine-124 PET lesion imaging

Abstract: The use of recovery coefficients (RCs) in (124)I PET lesion imaging is a simple method to correct the imaged activity concentration (AC) primarily for the partial-volume effect and, to a minor extent, for the prompt gamma coincidence effect. The aim of this phantom study was to experimentally investigate a number of various factors affecting the (124)I RCs. Three RC-based correction approaches were considered. These approaches differ with respect to the volume of interest (VOI) drawn, which determines the imag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
38
0
16

Year Published

2010
2010
2016
2016

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 44 publications
(55 citation statements)
references
References 42 publications
1
38
0
16
Order By: Relevance
“…The PET images were retrospectively reconstructed using parameters optimized for quantitative 124 I imaging (15). The emission images were reconstructed after Fourier rebinning using the iterative attenuation-weighted ordered-subset expectation maximization algorithm with 4 iterations and 16 subsets.…”
Section: Image Acquisition and Reconstructionmentioning
confidence: 99%
“…The PET images were retrospectively reconstructed using parameters optimized for quantitative 124 I imaging (15). The emission images were reconstructed after Fourier rebinning using the iterative attenuation-weighted ordered-subset expectation maximization algorithm with 4 iterations and 16 subsets.…”
Section: Image Acquisition and Reconstructionmentioning
confidence: 99%
“…Several groups have concluded that quantitation of 124 I PET images is feasible (7)(8)(9)(10)(11). Compared with 131 I SPECT, 124 I PET imaging offers a higher image spatial resolution, increased counting rate sensitivity, and higher quantitative capacity, resulting in the application of pretherapeutic 124 I PET/CT-based lesion dosimetry (12)(13)(14)(15)(16)(17).…”
mentioning
confidence: 99%
“…Finally, isovolume-RC uses the average of all voxel values equalling physical volume of the targets. 21 According to the PVE correction, different 90 Y-RC curves were defined taking into account different S/N, to evaluate the background spill-in effects.…”
Section: Introductionmentioning
confidence: 99%